The fractionation of adipose tissue procedure to obtain stromal vascular fractions for regenerative purposes - van Dongen, Joris A.; Stevens, Hieronymus P.; Parvizi, Mojtaba; van der Lei, Berend; Harmsen, Martin C. (Wound repair and regeneration, 2016)
Autologous adipose tissue transplantation is clinically used to reduce dermal scarring and to restore volume loss. The therapeutic benefit on tissue damage more likely depends on the stromal vascular fraction of adipose tissue than on the adipocyte fraction. This stromal vascular fraction can be obtained by dissociation of adipose tissue, either enzymatically or mechanical. Enzymatic dissociation procedures are time‐consuming and expensive. Therefore, we developed a new inexpensive mechanical dissociation procedure to obtain the stromal vascular fraction from adipose tissue in a time sparing way, which is directly available for therapeutic injection. This mechanical dissociation procedure is denoted as the fractionation of adipose tissue (FAT) procedure. The FAT procedure was performed in eleven patients. The composition of the FAT‐stromal vascular fraction was characterized by immunohistochemistry. Adipose derived stromal cells isolated from the FAT‐stromal vascular fraction were compared with adipose derived stromal cells isolated from nondissociated adipose tissue (control) for their CD‐surface marker expression, differentiation and colony forming unit capacity. Case reports demonstrated the therapeutic effect of the FAT‐stromal vascular fraction. The FAT‐stromal vascular fraction is an enrichment of extracellular matrix containing a microvasculature and culturable adipose derived stromal cells. Adipose derived stromal cells isolated from FAT‐stromal vascular fraction did not differ from adipose derived stromal cells isolated from the control group in CD‐surface marker expression, differentiation and colony forming unit capacity. The FAT procedure is a rapid effective mechanical dissociation procedure to generate FAT‐stromal vascular fraction ready for injection with all its therapeutic components of adipose tissue: it contains culturable adipose derived stromal cells embedded in their natural supportive extracellular matrix together with the microvasculature.